Respuesta :

Answer:

[tex]1. log_3(cd)^4  = 4 log_3(c )+ log_3(d)[/tex]  FALSE

[tex]2. \frac{2}{3} (ln(a) +ln(b)) =  ln(\sqrt[3]{a^2b^2} )[/tex]  TRUE

[tex]3.ln(\frac{e^3}{f} )  = 3 ln(e) - ln (f)[/tex]  TRUE

Step-by-step explanation:

Here, let us first state the logarithmic rules.

[tex]log (a) - log (b)  =log(\frac{a}{b} )\\log (ab)   = log a + log b\\log(a^m) = m \times log (a)[/tex]

Now, here the given expressions are:

[tex]1. log_3(cd)^4  = 4 log_3(c )+ log_3(d)[/tex]

The given statement is FALSE as:

[tex]log_3(cd)^4   = 4 log_3(cd)  = 4log_3(c) + 4log_3(d)[/tex]

[tex]2. \frac{2}{3} (ln(a) +ln(b)) =  ln(\sqrt[3]{a^2b^2} )[/tex]

[tex]\frac{2}{3} (ln(a) +ln(b))  =  \frac{2}{3} ln(ab)   =  ln(ab) ^\frac{2}{3}  \\= ln(\sqrt[3]{a^2b^2} )\\\implies\frac{2}{3} (ln(a) +ln(b)) =  ln(\sqrt[3]{a^2b^2} )[/tex]

The given statement is TRUE .

[tex]3.ln(\frac{e^3}{f} )  = 3 ln(e) - ln (f)[/tex]

The given statement is TRUE as:

[tex]ln(\frac{e^3}{f} )  =   ln(e^3) - ln (f)   =  3 ln(e) - ln (f)[/tex]